2018
DOI: 10.1039/c8ce01152d
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative structure direction of organosilanes and tetrapropylammonium hydroxide to generate hierarchical ZSM-5 zeolite with controlled porous structure

Abstract: Hierarchical ZSM-5 zeolites of controlled porous structure were realized by the cooperative direction of organosilanes and tetrapropylammonium hydroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The EDS analysis shown in Figure S14 also confirms the successful incorporation of Fe and Ga species. Meanwhile, the UV–vis spectrum and B MAS NMR results shown in Figure S15 and Figure S16 also confirm the existence of framework Fe, Ga, and B species and the successful synthesis of high-amount Fe-, Ga-, and B-doped hollow silicate-1. , …”
Section: Results and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The EDS analysis shown in Figure S14 also confirms the successful incorporation of Fe and Ga species. Meanwhile, the UV–vis spectrum and B MAS NMR results shown in Figure S15 and Figure S16 also confirm the existence of framework Fe, Ga, and B species and the successful synthesis of high-amount Fe-, Ga-, and B-doped hollow silicate-1. , …”
Section: Results and Discussionmentioning
confidence: 66%
“…Meanwhile, the UV−vis spectrum and B MAS NMR results shown in Figure S15 and Figure S16 also confirm the existence of framework Fe, Ga, and B species and the successful synthesis of high-amount Fe-, Ga-, and B-doped hollow silicate-1. 54,55 3.8. Catalytic Test for the Aldol Condensation.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, all the samples exhibited a sharp increase in nitrogen uptakes in a relatively low pressure of P/P 0 < 0.01, which indicated the presence of a microporous structure. 32 The samples prepared in the presence of TPOAC showed an enhanced uptake in the region of P/P 0 > 0.4, 33 corresponding to typical characteristics of mesopore materials. Moreover, the Barrett−Joyner−Halenda (BJH) method was adopted to investigate pore size distributions of the prepared beta zeolites, as shown in Figure S1.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…[106] The same TPOAC, but now in combination with TPAOH, was studied by Shen et al, who showed different morphologies by adjusting the composition of the synthesis mixture, in this way catalysts with nanorod morphologies and wormlike intracrystalline mesopores were created. [107] In another study, Xing et al used an acid treated kaolin clay as an Al and Si source in combination with organosilanes. Hexadecyltrimethoxysilane was added as a mesoporogen in a SAC method.…”
Section: Zsm-5mentioning
confidence: 99%